A simple model for chaos studies in nonlinear feedback systems - Uçar, Ahmet (My University, 2001)
Several models have been proposed in order to enlarge the class of nonlinear phenomena. In this article, a simple model is proposed for chaos studies in nonlinear feedback systems. The model consists of a state, time delay and a nonlinear element. It can be described as an autonomous continuous-time difference-differential equation with only one variable. The richness of such system behaviour is numerically illustrated and chaotic behaviour is presented. The computer generated chaos for the double-scroll attractor and bifurcation diagram are provided.
Jednostavan model za prou?avanje kaosa kod nelinearnih sustava s povratnom vezom
Keywords: Bifurcation diagram; Model for chaos; Nonlinear feedback systems; Time delay